Space Available for Cord, Motion, and disc degeneration at the adjacent segments level of degenerative cervical spondylolisthesis using kinematic MRI. (November 2017) - Paholpak, Permsak; Nazareth, Alexander; Barkoh, Kaku; Lee, Larry V.; Lucas, Joshua; Buser, Zorica; Wang, Jeffrey C.
Highlights: Cervical degenerative spondylolisthesis altered cervical spine kinematic. The cephalad level had the least disc degeneration and most translation motion overall. The spondylolisthesis level had the narrowest space available for cord. The likelihood of adjacent degeneration and spinal cord compression was higher in grade 2 spondylolisthesis. Abstract: The objective was to evaluate motion, disc degeneration and Space Available for Cord (SAC) at the adjacent segments of degenerative cervical spondylolisthesis (DCS) using kinematic Magnetic Resonance Imaging (kMRI). The cervical spine kMRI of sixty-one DCS spinal levels (38 anterolisthesis and 23 retrolisthesis) were analyzed at the listhesis level and its adjacent segments in three position using kMRI. MRAnalyzer3 was used to analyze translation, angular motion and SAC. The caudad level had significantly less translation motion than the listhesis level in overall DCS or grade 2 anterolisthesis group (P < 0.05). The cephalad level had significant more translational motion than the caudad level in overall DCS or grade 1 retrolisthesis group (P < 0.05). For disc degeneration, the cephalad level had the least disc degeneration and showed significant difference with the listhesis level in overall DCS or overall anterolisthesis or overall retrolisthesis or grade 2 anterolisthesis or grade 1 or 2 retrolisthesis (P < 0.05). For SAC, the listhesis level had the narrowest space in overall DCS groups. In neutral position, grade 1 anterolisthesis had significantly larger SAC at the listhesis and the cephalad level than grade 1 retrolisthesis (P < 0.05). In conclusion, DCS affected cervical spine motion and kinematics. Grade 1 retrolisthesis showed tendency of narrower SAC at the cephalad level more than the same grade anterolisthesis. The likelihood of the adjacent segment disease and spinal cord compression are higher in both grade 2 anterolisthesis and retrolisthesis.